Enhanced open shortest path first (OSPF) protocol using parallel tabu search - ring in wimax mesh network - Ahmed, Bilal Abdulhaq (2013)
Wireless mesh networks (WMNs) considered as self – organized, self – configured networks, and easily deployed ad hoc networks. Many ad hoc routing protocols were applied to WMNs and many studies were conducted to analyse the functionality of such networks. Many studies have been done on ad hoc routing protocols in WIMAX environment especially OSPF due to its widely available in the real network implementation. However, there was no comparison been made between OSPF and other ad hoc routing protocols such as DSDV, and OLSR in WIMAX environment using mesh mode specifically in term of throughput, end to end delay, delivery ratio, and packet drop. . As the technology of WIMAX using mesh mode is quite immature, this study is aimed to investigate and compare the capability of OSPF with other ad hoc protocols in such technology environment. On the other hand, OSPF uses link bandwidth to assign the cost metric in an inversely proportional manner, while the delay is considered an important factor to determine the link cost. This study is intended to contribute for OSPF protocol optimization by presenting new cost function depend on both delay and bandwidth dedicated for WIMAX using mesh mode In this study a performance analyses has been made among Optimized Link State Routing (OLSR) protocol, Destination-Sequenced Distance Vector (DSDV) routing protocol, and an intra-domain link-state of Open Shortest Path First (OSPF). The analysis has been made under WIMAX environment using mesh mode. In our simulation, 10 to 50 mesh nodes were arranged in a mesh topology, with a working area of 500 meter x 500 meter. The transmission range of each node is 250 meters. The NS2 version 2.33 has been used as our simulator. It was found that the conventional OLSR has the worst performance when it’s compared to OSPF and DSDV in term of End to End delay, delivery ratio and drop ratio. The results showed the proposed extension of OSPF has better results than the conventional OSPF in terms of all the above parameters including the throughput.